Omega-3 fatty acids determination in eyeballs, heads and livers of pond-cultured milkfish (chanos chanos) - Guirgen, Ruvir L. (College of Fisheries, University of the Philippines, 2000)
In milkfish processing, not all fish body parts are utilized. Hence, considered as wastes. Based on actual experiment, heads, eyeballs, and livers account to about 6.37, 2.10 and 1.75% of the total milkfish body weight respectively. These wastes ,may be containing significant amount of nutritionally important nutrients that area vital to human health development e.g. omega-3 fatty acid composition of the milkfish eyeballs, heads and livers and its implication to human health. Based on the results, livers were found to contain large quantities of omega-3 fatty acids (5.3%), which is 1.74% greater than the heads (3.56%). Total lipid contents of the samples were also determined. Livers were found to give highest lipid content (17.37%), which is 6% greater than the heads were done in order to determine the quality of oils extracted. Low peroxide values, acid values, and TBA indicate that the lipids extracted from eyeballs, heads and livers of milkfish were not rancid.